Screening, identification and tolerance of enzyme and aroma-producing mold from light-flavor Baijiu Daqu - HE Yimin, MOU Feiyan, ZHANG Wei, LIAO Bei, DONG Xiaoyuan, LI Junwei, FANG Shangling, CHEN Maobin (Zhongguo niangzao)
The molds were isolated from light-flavor (Qingxiangxing) Baijiu Daqu by traditional culture and separation technology combined with morphological observation, and the molds with superior enzyme and aroma production performance were screened by analyzing the saccharification power, liquefaction power, esterification power, lipase activity and aroma production ability. The selected strain was identified by molecular biological techniques, and their tolerance to high temperature, pH and ethanol were analyzed. The results showed that a total of 6 strains of mold were isolated from light-flavor Daqu, and one strain named as MJ-5 with superior enzyme and aroma production performance was screened. The strain MJ-5 was cultured in bran medium at 30 ℃ for 3 d, the saccharification power was 258.02 U/g, the liquefaction power was 0.42 U/g, the esterification power was 44.51 U/g, and the lipase activity was 8.98 U/g. The relative contents of ethyl phenylacetate (15.7%) and ethyl laurate (1.74%) in the Fuqu fermented with strain MJ-5 were higher, which helped to increase the fruit flavor of Baijiu. In addition, the (-)-alpha-guassene (0.96%) was also detected. The strain MJ-5 was identified as Lichtheimia ramosa, which had good tolerance and could tolerance high temperature 39 ℃, pH 4 and ethanol volume fraction 6%.